Improving Students' Learning Enthusiasm By Using The Snowball Throwing Learning Model in The Science Subject of Sound Energy in Grade IV of SDN 4 Puyung Trenggalek - ribud setiawan; Raden Syaifuddin; Sri Utami (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to increase students' enthusiasm for learning by using the snowball throwing learning model in sound energy science subjects. And to find out the implementation of learning using the Snowball Throwing learning model in increasing students' enthusiasm for learning in the Sound Energy Science subject class IV at SDN IV Puyung. To improve and increase students' learning enthusiasm using the Snowball Throwing learning model in the Sound Energy Science subject class IV SDN IV Puyung. Therefore, education that is oriented towards elementary schools requires renewal and innovation in the teaching process so that it is not just taking notes, listening, lecturing and so on. As is the case at Puyung IV State Elementary School (SDN), which is in Puyung Village, Pule District, Trenggalek Regency, in the learning process they are still taking notes and listening to lectures, therefore changes need to be made. New innovations are really needed to increase students' enthusiasm for learning so that their achievements increase. Based on the results of studies conducted at SDN IV Puyung Trenggalek, students have shown high enthusiasm for learning. They can take part in lessons enthusiastically and make the best use of every opportunity given by the teacher. Students appear active in answering every question asked by the teacher, and students appear enthusiastic in participating in every learning process.  This can be proven by the success of students in learning by showing activeness, enthusiasm and enthusiasm, as well as understanding in carrying out tasks well